EFEKTIFITAS KOMUNIKASI SBAR TERHADAP PENCEGAHAN RISIKO JATUH DI RUANG RAWAT INAP CEMARA 1 RS. BHAYANGKARA TK. 1 R. SAID SUKANTO - Nada Mutiara, (2022)
SBAR communication is communication made by nurses in conveying the patient's condition. Communication on the receipt must be delivered clearly and effectively. If the weigh-in is carried out with ineffective communication, it can lead to patient safety incidents such as falls. The results of the study conducted in the Cemara Room 1 showed that the application of communication during weighing and receiving was less effective. The results of the Pre Test using the SBAR communication questionnaire showed that 5 out of 13 nurses (38.5%) had poor communication practices, so an intervention in the form of education regarding the application of SBAR communication in preventing the risk of falls was carried out for 3 days. The results of the Post Test questionnaire showed an increase (38,5%) in the application of SBAR communication in preventing the risk of falling. These results indicate that there is an effectiveness of SBAR communication in preventing the risk of falling in the inpatient room. Recommendations nurses need to apply good SBAR communication during weighing in order to avoid unwanted events, especially the risk of falling and can conduct training on the application of SBAR communication and fall risk prevention.